Demystified . . . Human endogenous retroviruses. Issue 1 (1st February 2003) - Nelson, P N; Carnegie, P R; Martin, J; Davari Ejtehadi, H; Hooley, P; Roden, D; Rowland-Jones, S; Warren, P; Astley, J; Murray, P G
Abstract : Human endogenous retroviruses (HERVs) are a family of viruses within our genome with similarities to present day exogenous retroviruses. HERVs have been inherited by successive generations and it is possible that some have conferred biological benefits. However, several HERVs have been implicated in certain cancers and autoimmune diseases. This article demystifies these retroviruses by providing an insight into HERVs, their means of classification, and a synopsis of HERVs implicated in cancer and autoimmunity. Furthermore, the biological roles of HERVs are explored.